THE EFFECT OF NATIVE LIPOSOMES AND “MEMBRANOSTABIL” PREPARATION ON PROTEIN EXPRESSION OF CALVES’ ENTEROCYTES PLASMOLEMMA DURING THE FORMATION OF COLOSTRUM IMMUNITY - Holopura, S. I.; Tsvilikhovsky, M.I. (Scientific Progress & Innovations, 2019)
The indices of expression of proteins with molecular weight of 50−75 kDa in enterocytes plasmolemma of the newborn calves’ empty jejunum, then 6 and 24 hours after birth were investigated. The study was per-formed on calves of three groups (control and two experimental ones) of the Ukrainian black-and-white dairy breed. The calves of the first experimental group were given native soybean phospholipid bilayer lipo-somes based on soybean lecithin with colostrum, and the calves in the second experimental group received “Membranostabil” preparation developed by our research group on the basis of soybean leci-thin.“Membranostabil” is a preparation consisting of phospholipid bilayer macro-capsules filled with wa-ter-soluble forms of A and E vitamins. The test samples of jejunum enterocytes were taken from newborn calves before the first colostrum feeding and 6 and 24 hours after birth. The protein expression of the mem-brane lysates’ fraction in isolated enterocytes of the calf jejunum was determined by electrophoresis. The percentage of separate protein fractions were determined by densitometry method using TotalLab software. Statistical processing of the study results and correlation between IgM content and the enterocytes plasmo-lemma proteins with molecular weights of 50−75 kDa was conducted using the Microsoft Excel 2016 com-puter program. It was found that application of native soybean phospholipid bilayer liposomes based on lecithin and “Membranostabil” preparation for newborn calves with colostrum contributed to the prolonga-tion of the expression time of enterocytes plasmolemma proteins with molecular weight of 50–75 kDa as compared with those in calves of the control group. The dynamics of expression of proteins with molecular weight of 50–75 kDa in the enterocytes plasmolemma of the jejunum in calves of the control and experi-mental groups with and without the effect of the investigated agents was shown. The correlation between IgM content in blood serum of calves in the control and experimental groups and expression of enterocytes plasmolemma proteins with molecular weight of 50–75 kDa was shown. It was proven that giving native soybean phospholipid bilayer liposomes based on lecithin and “Membranostabil” preparation to calves con-tributed to increasing IgM content in the blood serum of the animals.